A cross-sectional study on prevalence of hypertension among college going degree students in urban Khammam, Telangana - Chennuri, Harish; Goud, K. Sujana; Bhavani, Kotra Siri (International Journal Of Community Medicine And Public Health, 2021)
Background: Hypertension is important cause for globally contributing more than 40% to cardiac related deaths worldwide. The increase of hypertension in the developing countries may be connected with the economic transition The primary aim of this study was to determine the prevalence of hypertension among young adults such as college going degree students in urban Khammam, Telangana, India in relation to the socio-demographic variables associated with hypertension including age, sex, socio-economic status, body mass index, dietary habits, tobacco use and alcohol consumption. Methods: This study was a cross-sectional was conducted to determine the prevalence and pattern of hypertension among 625 college going degree students in urban Khammam, Telangana, area. Results: 625 students participated out of which 51.52% were males and 48.48% were females. The prevalence among males was higher as compared to females and found to be statistically significant (p<0.001). In the present study, associated factors like gender, age, marital status, occupation, education status, tobacco use, and physical activity were significantly associated with the hypertension status of the study subjects. Conclusions: This study establishes the prevalence of hypertension among males was higher compared to females. The socio-demographic variables such as dietary habits, BMI, alcohol and tobacco consumption play a pivotal role in the prevalence of hypertension.